229k views
2 votes
C(n) =-9/2 (-4/3) n-1
What is the 2 term in the sequence?

User RafaelGP
by
5.2k points

1 Answer

5 votes

Answer:

c(2)=6

Explanation:

The explicit formula for the sequence is:


c(n) = - (9)/(2) ( { - (4)/(3) })^(n - 1)

To find the 2nd term, we substitute n=2 to get:


c(2) = - (9)/(2) ( { - (4)/(3) })^(2- 1)

We simplify to obtain:


c(2) = - (9)/(2) ( { - (4)/(3) })^(1)

This is the same as:


c(2) = - (9)/(2) ( { - (4)/(3) })

We cancel common factors to get:


c(2) = 3 * 2 = 6

User Benjamin Abt
by
5.5k points